Assessing the perception of face pareidolia in children (Homo sapiens), rhesus monkeys (Macaca mulatta), and capuchin monkeys (Sapajus apella) - Flessert, Molly; Taubert, Jessica; Beran, Michael J (Journal of comparative psychology (Washington, D.C. : 1983), 2023)
Face pareidolia is the misperception of a face in an inanimate object and is a common feature of the face detection system in humans. Whereas there are many similarities in how humans and nonhuman animals such as monkeys perceive and respond to faces, it is still unclear whether other species also perceive certain nonface stimuli as faces. We presented a novel computerized task to capuchin monkeys ( ), rhesus monkeys ), and preschool-aged children ( ). This task trained subjects to choose faces over nonface images, and then presented pareidolia images with nonface images. All species selected faces most often on trials that included face images. However, only children selected pareidolia images at levels above chance. These results indicate that while children report perceiving face pareidolia, monkeys do not. These species differences could be due to human-unique experiences that result in an increased aptitude for anthropomorphizing objects with face-like patterns. It could also be due to monkeys showing a greater reliance on stimulus features rather than global, holistically organized cues that faces provide. (PsycInfo Database Record (c) 2023 APA, all rights reserved).